Focusing on Resilience and Renewal From Stress: The Role of Emotional and Social Intelligence Competencies - Liu, Han; Boyatzis, Richard E. (Frontiers in Psychology, 2021)
Individuals are subject to stressful events from daily chronic stress to traumatic life-changing experiences and the resulting impairment. Efforts to reduce stress or stressors are misdirected. Instead, bouncing back or recovering from such experiences, often called resilience is a far more potent way to ameliorate the ravages of chronic stress and move to a state of renewal, thriving and flourishing. Because we infect each other with stress or renewal through emotional contagion, each person’s ability to manage their own emotions as well as those of others and their relationships becomes key to health. These capabilities are called emotional and social intelligence. At the trait level, they are personal dispositions but at the behavioral level they are patterns of behavior we call emotional and social intelligence competencies (ESI). This paper is a review addressing the role of emotional and social intelligence competencies in resilience. By focusing on the behavioral level of ESI, designs for more precise research and practical applications as to how to develop ESI and resilience are offered.